PRIMARY STRUCTURE OF WHEAT GERM PHENYLALANINE TRANSFER RNA - Dudock, Bernard S. (1969)
The complete nucleotide sequence of wheat germ phenylalanine transfer RNA (tRNA(Phe)) is presented. This RNA, which is an acceptable substrate for yeast phenylalanine tRNA synthetase, has a structure very similar to that of yeast tRNA(Phe). Only 16 of the 76 nucleotides are different, and all but two of the nucleotide changes are located in regions that are doublestranded in the cloverleaf model. The two changes in single-stranded regions involve minor modifications of the same nucleotide. The dihydrouridine loop and its supporting stem are completely free of nucleotide changes.